Monitoring the Indian meal moth Plodia interpunctella in a rice-milling factory - MIYANOSHITA, Akihiro (Urban Pest Management, 2023)
I investigated the abundance and distribution of Indian meal moth adults in a rice-milling factory in the Kanto region of Japan for two years from March 2020 using sex pheromone traps. One trap was set up outside the factory and four traps inside it (in the cleaning and separation, brown rice storage, rice milling, and bran storage areas). The traps, which were replaced monthly, captured 5.47 / day moths in the first year and 4.36 / day moths in the second. The moths were captured from March to November; the peak was in August. The rice milling area was where the greatest number of moths was captured in both years.